Analytical and numerical models of the magnetoacoustic tomography with magnetic induction. Issue 2 (5th March 2018) - Ziolkowski, Marcin; Gratkowski, Stanislaw; Zywica, Adam Ryszard
Abstract : Purpose: Electrical properties of biological tissues are known to be sensitive to physiological and pathological conditions of living organisms. For instance, human breast cancer or liver tumor cells have a significantly higher electrical conductivity than a healthy tissue. The paper aims to the new recently developed magnetoacoustic tomography with magnetic induction (MAT-MI) which can be deployed for electrical conductivity imaging of low-conductivity objects. Solving a test problem by using an analytical method is a useful exercise to check the validity of the more complex numerical finite element models. Such test problems are discussed in Chapter 3. The detailed analysis of an electromagnetic induction in low-conductivity objects is very important for the next steps in the tomographic process of image reconstruction. Finally, the image reconstruction examples for object's complex shapes' have been analyzed. The Lorentz force divergence reconstruction has been achieved with the help of time reversal algorithm. Design/methodology/approach: In given arrangements the magnetic field and eddy current vectors satisfy the Maxwell partial differential equations. Applying the separation of variables method analytical solutions are obtained for an infinitely long conducting cylindrical segment in transient magnetic field. A special case for such a configuration is an infinitely long cylinder with longitudinal crack. The analytical solutions are compared with those obtained by using numerical procedures. For complex shapes of the object, the MAT-MI images have been calculated with the help of the finite element method and time reversal algorithm. Findings: The finite element model developed for a MAT-MI forward problem has been validated by analytical formulas. Based on such a confirmation, the MAT-MI complex model has been defined and solved. The conditions allowing successful MAT-MI image reconstruction have been provided taking into account different conductivity distribution. For given object's parameters, the minimum number of measuring points allowing successful reconstruction has been determined. Originality/value: A simple test example has been proposed for MAT-MI forward problem. Analytical closed-form solutions have been used to check the validity of the made in-house finite element software. More complex forward and inverse problems have been solved using the software.